Effect of Zinc Doping on the Electrical and Dielectric Properties of CCTO Compound Synthesized by Solid-State Method - Slaoui, M.; Gouitaa, N.; El Issmaeli, Y.; Harrach, A.; Abdi, F.; Haddad, M.; Lamcharfi, T. (Asian Journal of Chemistry, 2021)
In this work, the influence of zinc doping on structural and dielectric properties of CaCu(3-x)ZnxTi4O12 (CCZxTO with x = 0, 2.5, 5, 7.5, 10, 12.5 and 15%) ceramics sintered at 1000 ºC for 8 h was studied. The ceramic samples were prepared by the conventional solid-state and calcined at 1050 ºC for 4 h. The X-ray diffraction (XRD) analysis of pure and Zn-doped CCTO were analyzed by using Rietveld refinement with cubic CCTO phase with no trace impurity phase. The scanning electron microscopy (SEM) investigation showed that for Zn-doped CCTO, the grains distributions were homogenous with average sizes which decreased with increasing of Zn concentration. The dielectric permittivity as function of temperature showed two dielectric anomalies (weakly and strong) and the dielectric constant value largely decreased for x = 2.5%, which is about tree magnitude smaller than the pure ceramic. Then it increased and reached a maximum at x = 10%, which is larger than the value of pure ceramic. And for x > 10%, the dielectric constant decreased for about two magnitude smaller than the ceramic at x = 10%. The cole-cole diagramm for all the samples showed existence of two semi-arcs attributed to the grains and grains boundaries. It was found that the Rg values were much smaller than the Rgb value. This give an evidance on the formation of interior barrier layer capacity (IBLC).